2023
DOI: 10.1001/jamanetworkopen.2023.27429
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Ethnic Disparities in Survival Among People With Second Primary Cancer in the US

Abstract: ImportanceComprehensive data for racial and ethnic disparities after second primary cancers (SPCs) are lacking despite the growing burden of SPCs.ObjectiveTo quantify racial and ethnic disparities in survival among persons with SPCs.Design, Setting, and ParticipantsThis population-based, retrospective cohort study used data from 18 Surveillance, Epidemiology, and End Results registries in the US for persons diagnosed with the most common SPCs at age 20 years or older from January 1, 2000, to December 31, 2013 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 94 publications
0
2
0
Order By: Relevance
“…Our regional analysis that followed revealed that although the ASDR for CC has decreased in all areas in recent years, regions with high SDI levels have experienced greater decrease, which benefited more than those with lower SDI levels. It suggests that the geographic factor and its socioeconomic correlates are the key stratification parameter [ 20 ]. Singh et al suggested that there are global inequalities in CC mortality due to human development, social inequalities, and differences in living standards [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our regional analysis that followed revealed that although the ASDR for CC has decreased in all areas in recent years, regions with high SDI levels have experienced greater decrease, which benefited more than those with lower SDI levels. It suggests that the geographic factor and its socioeconomic correlates are the key stratification parameter [ 20 ]. Singh et al suggested that there are global inequalities in CC mortality due to human development, social inequalities, and differences in living standards [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Federica et al [ 5 ] found that the oral cavity and oropharynx were more common as index sites in the head and neck region (43% and 31%, respectively). Various factors play key roles in the development of multiple malignancies, such as genetics, hormones, prior cancer treatment exposure, and detrimental lifestyle factors (e.g., smoking and alcohol) [ 6 , 7 ]. Upon searching the PubMed database, we identified seven cases of four or more primary tumors from 2010 to 2023 (summarized in Table S 2 ).…”
mentioning
confidence: 99%